Is befriending a valuable intervention in schizophrenia? A scoping review - Farcas, Adriana; Campbell, Mackenzie; Wong, Charmaine; Iftene, Felicia (Frontiers in Psychiatry, 2023)
Background: Schizophrenia is a severe, chronic mental disorder that involves disruptions in thought processes, perceptions, emotional responsiveness, and social interactions. Psychotherapeutic and social integration practices have increasingly been added to the pharmacological treatment in an effort to improve the level of functioning and the quality of life of individuals affected by this condition. Befriending, defined as a one-on-one companionship provided by a volunteer who aims to act as an emotionally supportive liaison, is hypothesized to be an effective such intervention, offering support for building and maintaining social relationships in the community. Despite its increase in popularity and acceptance, befriending remains poorly understood and under-researched. Methods: We performed a systematic search for studies targeting befriending either as an intervention or a controlled condition in studies on schizophrenia. Searches were performed in four databases: APA PsycInfo, Pubmed, Medline and EBSCO. The keywords “schizophrenia”, AND “befriending”, were searched for on all databases. Results: The search yielded 93 titles and abstracts, of which 18 met the criteria for inclusion. The studies included in this review have all incorporated befriending as an intervention or a controlled condition, as per our search criteria, and aimed at depicting the value and feasibility of this intervention to address social and clinical deficits in individuals with schizophrenia. Conclusions: The studies selected for this scoping review revealed inconsistent findings regarding the effect of befriending on overall symptoms and the subjective reporting of quality of life in individuals with schizophrenia. This inconsistency may be attributed to differences between the studies and their specific limitations.